Impact of exercise training associated with enalapril treatment on blood pressure variability and renal dysfunctions in an experimental model of arterial hypertension and postmenopause. - Michel Pablo Dos Santos Ferreira Silva; Maycon Junior Ferreira; Tânia Plens Shecaira; Danielle da Silva Dias; Débora Conte Kimura; Maria Cláudia Irigoyen; Guiomar Nascimento Gomes; Kátia De Angelis (PLoS ONE, 2024)
Objective In this study, we aimed to investigate the effects of the concurrent exercise training (CET) associated with the enalapril maleate on blood pressure variability (BPV) and renal profile in an experimental model of arterial hypertension (AH) and postmenopause. Methods Female ovariectomized spontaneously hypertensive rats (SHR) were distributed into 4 groups (n = 8/group): sedentary (SO), sedentary + enalapril (SOE), trained (TO) and trained + enalapril (TOE). Both enalapril (3mg/kg) and CET (3 days/week) were conducted during 8 weeks. Blood pressure (BP) was directly recorded for BPV analyses. Renal function, morphology, inflammation and oxidative stress were assessed. Results The SOE, TO e TOE groups presented decreased systolic BP compared with SO. Both trained groups (TO and TOE) presented lower BPV and increased baroreflex sensitivity (TO: 0.76 ± 0.20 and TOE: 1.02 ± 0.40 vs. SO: 0.40 ± 0.07 ms/mmHg) compared with SO group, with additional improvements in TOE group. Creatinine and IL-6 levels were reduced in SOE, TO and TOE compared with SO group, while IL-10 was increased only in TOE group (vs. SO). Enalapril combined with CET promote reduction in lipoperoxidation (TOE: 1.37 ± 0.26 vs. SO: 2.08 ± 0.48 and SOE: 1.84 ± 0.35 μmol/mg protein) and hydrogen peroxide (TOE: 1.89 ± 0.40 vs. SO: 3.70 ± 0.19 and SOE: 2.73 ± 0.70 μM), as well as increase in catalase activity (vs. sedentary groups). The tubulointerstitial injury was lower in interventions groups (SOE, TO and TOE vs. SO), with potentialized benefits in the trained groups. Conclusions Enalapril combined with CET attenuated BPV and baroreflex dysfunctions, probably impacting on end-organ damage, as demonstrated by attenuation in the AH-induced renal inflammations, oxidative stress and morphofunctional impairments in postmenopausal rats.